2019
DOI: 10.1016/j.gloplacha.2019.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Integration of multi-archive datasets for the development of a four-dimensional paleoflood model of alpine catchments

Abstract: Both natural and documentary evidence of severe and catastrophic floods are of tremendous value for completing multidimensional flood calendars, as well as for mapping the most extreme riverine flooding phenomena in a river basin, over centennial and millennial time scales. Here, the integration of multi-archive flood series from the Hasli-Aare, Lütschine, Kander, Simme, Lombach, and Eistlenbach catchments in the Bernese Alps constitutes a unique approach to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 47 publications
2
3
0
1
Order By: Relevance
“…The existence of flood-rich periods in the last 500 years has been demonstrated for a number of individual catchments in Europe based on historical documentary evidence 5,6,7,8 and mountain lake sediments 9 . One of the few available regional studies (19 documentary-based data series) identified 1540-1600, 1640-1700, 1730-1790 and 1790-1840 as flood-rich periods in Central Europe 2 , which is roughly consistent with sedimentary evidence from a set of Alpine lakes 10 and six floodplains 11 in Central Europe. Several authors have suggested that more frequent flooding in the Little Ice Age (1300-1870), and specifically the late Maunder Solar Minimum (1675-1725), can be related to lower air temperatures 6,2,12,8 , but a more universal relationship with air temperatures for other flood-rich periods has not been identified 7,13,11 .…”
Section: Historical Flood Contextsupporting
confidence: 61%
See 1 more Smart Citation
“…The existence of flood-rich periods in the last 500 years has been demonstrated for a number of individual catchments in Europe based on historical documentary evidence 5,6,7,8 and mountain lake sediments 9 . One of the few available regional studies (19 documentary-based data series) identified 1540-1600, 1640-1700, 1730-1790 and 1790-1840 as flood-rich periods in Central Europe 2 , which is roughly consistent with sedimentary evidence from a set of Alpine lakes 10 and six floodplains 11 in Central Europe. Several authors have suggested that more frequent flooding in the Little Ice Age (1300-1870), and specifically the late Maunder Solar Minimum (1675-1725), can be related to lower air temperatures 6,2,12,8 , but a more universal relationship with air temperatures for other flood-rich periods has not been identified 7,13,11 .…”
Section: Historical Flood Contextsupporting
confidence: 61%
“…One of the few available regional studies (19 documentary-based data series) identified 1540-1600, 1640-1700, 1730-1790 and 1790-1840 as flood-rich periods in Central Europe 2 , which is roughly consistent with sedimentary evidence from a set of Alpine lakes 10 and six floodplains 11 in Central Europe. Several authors have suggested that more frequent flooding in the Little Ice Age (1300-1870), and specifically the late Maunder Solar Minimum (1675-1725), can be related to lower air temperatures 6,2,12,8 , but a more universal relationship with air temperatures for other flood-rich periods has not been identified 7,13,11 . Temperature anomalies can be considered a proxy for changes in the atmospheric circulation system and are therefore of relevance for assessing past and future flood frequency changes.…”
Section: Historical Flood Contextsupporting
confidence: 61%
“…Issues identified in the current synthesis include (1) low resolution palaeoclimatic data, (2) limited age control depending on dating techniques and uncertainties, (3) unevenly spaced time series, which can include time lags and gaps, (4) conflicting information from multiple proxies, and (5) alteration by land use changes. See Lüning et al () and Schulte et al () for more detailed discussions. Many paleoclimate records on land retrieved form lakes, lagoons, peatland, and so on, may be influenced since the 11th century by increasing local and regional land use changes and human perturbation as consequence of the rising foundation of cities and monasteries in many regions of Europe and in the Mediterranean.…”
Section: Methodsmentioning
confidence: 99%
“…Benito et al, 2004;Jones et al, 2012;Schulte et al, 2009), many only compare one archive with historical data. Studies that achieve spatial-temporal integration from more than one archive are comparably rare (Schulte et al, 2015;Schulte et al, 2019a). Our investigation not only demonstrates how a range of archives can be mined to shed light on spatial-temporal dynamics of a historic flood but it also successfully applies this technique in a part of the world where there are comparably few examples of multiproxy reconstructions (Schulte et al, 2019b).…”
Section: Insight Gained From the Integration Of Historical Geomorphol...mentioning
confidence: 79%